An Assessment of an early 19th century AD Ceramic Assemblage from Mozambique Island - Simbine, Celso Zefanias (Department of Archaeology, 2022)
In this dissertation, I present the results of my recent investigation of ceramics from Mozambique Island. This contributes to, and builds upon previous archaeological work that has made a start on describing and dating the ceramic sequence and linking it to the history of the south East African coast over the last 2000 years. The ceramics described and interpreted here come from two excavations. One sample is from within the precincts of a Muslim house, the Abdurrazaque Juma compound located within Macuti-town, south of the urban ‗stone town‘ to the north, where the second sample was excavated from the tribunal courtyard of the Convent of São Domingos. I used a multidimensional analysis to classify the ceramics. The ceramics from the muslim house are dominated by coarse earthenware vessels, and in particular by carinated open bowls. The bulk of this assemblage dates to the early 19th century AD and can be linked to a kitchen. The dominance of carinated bowls functionally indicates rice preparation and consumption and discussion of these ceramics focuses on the domestic context of the household and the work of servants, and possibly slaves. Ceramics from the second excavation provide comparative material that elaborates the ceramic sequence for the Island. This is particularly so for the carinated open bowls that through comparison with other sites along the east African coast, are frequently found in historical contexts dating between the ends of 16th to 20th centuries AD. As a proxy for rice agriculture, the ceramics reported on here contribute to this agricultural sequence and an association with enslaved African populations and elite foodways along East African Coast.